ANALISIS HUBUNGAN MEDIA VISUAL DENGAN PENINGKATAN HASIL BELAJAR DI SMK MUHAMMADIYAH BULUKUMBA - Muh. Nasrun (Almeera Education, 2024)
This study uses the ex post facto method, namely by taking data such as learning achievement value data based on the average before receiving treatment and after receiving treatment. The population in this study were 22 students of Class XII, Computer Engineering and Networking Department of Muhammadiyah Bulukumba Vocational School. To determine the sample size in this study using non-probability techniques, namely saturated sample techniques using the entire population as a sample, namely 22 students. Data collection techniques used are observation techniques, interviews, documentation and evaluation tests. The data analysis technique used is the arithmetic mean method. Thus, the arithmetic mean coefficient obtained an increase in the learning outcomes of Class XII students of the Computer and Network Engineering Department after receiving treatment, an increase of 2.69 from the original value obtained. The average learning outcomes of Class XII students majoring in Computer Engineering and Networking at Muhammadiyah Bulukumba Vocational School before treatment were 6.27 and the average achievement of Class XII students majoring in Computer Engineering and Networking at Muhammadiyah Bulukumba Vocational School after treatment was 8.96 with the field of study Computer Science.